Intestinal Barrier Healing Is Superior to Endoscopic and Histologic Remission for Predicting Major Adverse Outcomes in Inflammatory Bowel Disease: The Prospective ERIca Trial - Rath, Timo; Atreya, Raja; Bodenschatz, Julia; Uter, Wolfgang; Geppert, Carol E.; Vitali, Francesco; Fischer, Sarah; Waldner, Maximilian J.; Colombel, Jean-Frédéric; Hartmann, Arndt; Neurath, Markus F. (Gastroenterology (New York, N.Y. 1943), 2023)
Endoscopic and histologic remission have emerged as key therapeutic goals in the management of inflammatory bowel diseases (IBD) that are associated with favorable long-term disease outcomes. Here, we prospectively compared the predictive value of barrier healing with endoscopic and histologic remission for predicting long-term disease behavior in a large cohort of patients with IBD in clinical remission. At baseline, patients with IBD in clinical remission underwent ileocolonoscopy with assessment of intestinal barrier function by confocal endomicroscopy. Endoscopic and histologic disease activity, as well as barrier healing, was prospectively assessed along established scores. During subsequent follow-up, patients were closely monitored for clinical disease activity and the occurrence of major adverse outcomes (MAOs): disease flares, IBD-related hospitalization or surgery, and initiation or dose escalation of systemic steroids, immunosuppressants, small molecules, or biological therapy. The final analysis included 181 patients, 100 with Crohn’s disease [CD] and 81 with ulcerative colitis (UC). During a mean follow-up of 35 (CD) and 25 (UC) months, 73% of patients with CD and 69% of patients with UC experienced at least 1 MAO. The probability of MAO-free survival was significantly higher in patients with IBD with endoscopic remission compared with endoscopically active disease. In addition, histologic remission predicted MAO-free survival in patients with UC but not CD. Barrier healing on endomicroscopy was superior to endoscopic and histologic remission for predicting MAO-free survival in both UC and CD. Barrier healing is associated with decreased risk of disease progression in patients with clinically remittent IBD, with superior predictive performance compared with endoscopic and histologic remission. Analysis of barrier function might be considered as a future treatment target in clinical trials. ClinicalTrials.gov number, NCT05157750. Healing of the intestinal barrier is associated with decreased risk of disease progression of inflammatory bowel diseases, with superior prediction of the further course of disease by barrier healing compared to endoscopic and histologic remission.